Refactoring Informations Systems - Löwe, Michael; König, Harald; Peters, Michael; Schulz, Christoph (Electronic Communications of the EASST, 2007)
We present our formal framework for the refactoring of complete information systems, i.e., the data model and the data itself. It is described using general and abstract notions of category theory and can handle addition, renaming and removal of model objects as well as folding and unfolding within complete and partial object compositions.